Surface treatment method of cadmium telluride absorption layer, cadmium telluride power generation glass and manufacturing method of cadmium telluride power generation glass
The oxide layer on the surface of the cadmium telluride absorbing layer was removed through laser etching technology to form a pyramid-type suede structure, which solved the problems of rough surface treatment and low efficiency in the prior art, and achieved the improvement of the performance of cadmium telluride power generation glass.
Patent Information
- Application Number
- CN202411796980.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art When treating the surface oxide layer of the cadmium telluride absorbing layer, the method is rough and difficult to achieve uniform film surface, affecting the coverage and film formation quality of the back contact layer, and traditional liquid acid corrosion is time-consuming and burdening the environment.
The oxide layer on the surface of the cadmium telluride absorbing layer is removed by laser etching to form a pyramid-type suede structure, improve the contact quality between the absorbing layer and the back contact layer, and ensure that the height of the suede structure is between 5 and 80 nm by reasonably adjusting the laser parameters.
The trapped light structure is formed through laser etching, which improves the ohmic contact quality of the absorbing layer and the back contact layer, reduces the series resistance, and increases the short-circuit current, thereby improving the performance of cadmium telluride power glass.
Smart Images

Figure CN119698136A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cadmium telluride power generation glass manufacturing, and in particular to a surface treatment method of a cadmium telluride absorption layer, cadmium telluride power generation glass and a manufacturing method. Background Art
[0002] Cadmium telluride power generation glass is composed of a multi-layer structure, generally including a glass substrate, a transparent conductive film, a window layer, an absorption layer, a back contact layer and a back electrode layer. The back contact layer can reduce the Schottky barrier formed by the absorption layer and the back electrode layer to improve the performance of the power generation glass. However, before the back contact layer is formed, since the light absorption layer generally undergoes high-temperature activation and other processes, an oxide layer will form on the surface, which will increase the series resistance and be detrimental to the contact between the back contact layer and the light absorption layer.
[0003] In response to this situation, the existing technology often uses low-concentration acidic liquid to etch the surface to remove the oxide layer. However, this method does not accurately control the concentration, and the surface treatment of the light-absorbing layer is very rough, and it is impossible to achieve uniform film surface, resulting in large differences in the surface morphology of cadmium telluride, affecting the coverage of the back contact layer. At the same time, liquid residue affects the film quality of the back contact layer, and the surface structure morphology of the back contact layer is uncontrollable. The light trapping structure cannot be achieved, and conventional treatment methods are difficult to obtain high-quality back contact characteristics. In addition, traditional liquid acid etching is time-consuming, the cleaning efficiency is low, and the treatment of acid will also burden the environment. Summary of the invention
[0004] In order to solve the defects in the prior art, the present invention provides a surface treatment method of a cadmium telluride absorption layer, a cadmium telluride power generation glass and a manufacturing method. The present invention uses laser etching of the oxide layer on the surface of the cadmium telluride absorption layer to form a light trapping structure to improve light absorption, improve the high-quality ohmic contact between the light absorption layer and the back contact layer, reduce the series resistance, and increase the short-circuit current, thereby improving the performance of the cadmium telluride power generation glass.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a surface treatment method for a cadmium telluride absorption layer, wherein the oxide layer on the surface of the cadmium telluride absorption layer is etched by laser so that the cadmium telluride absorption layer forms a pyramid-shaped velvet structure, wherein the vertical height of the velvet structure is 5 to 80 nm.
[0007] In some embodiments of the present invention, the vertical height of the velvet structure is any one of 5 nm, 45 nm, 60 nm, 80 nm, or a value between the two.
[0008] Preferably, the laser is a pulsed laser with a wavelength of 532 nm.
[0009] Preferably, the laser light spot is a circular light spot.
[0010] Preferably, the pulse width of the pulse laser is 100-300 nm. In some embodiments of the present invention, the pulse width of the pulse laser is any one of 100 nm, 150 nm, 200 nm, 300 nm or a value in between.
[0011] Preferably, the frequency of the pulsed laser is 20-60 KHz. In some embodiments of the present invention, the frequency of the pulsed laser is any one of 20 KHz, 55 KHz, 40 KHz, 60 KHz or a value between the two.
[0012] Preferably, the pulse laser scanning speed is 3000-9000 mm / s. In some embodiments of the present invention, the pulse laser scanning speed is any one of 3000 mm / s, 6000 mm / s, 7000 mm / s, 9000 mm / s or a value in between.
[0013] Preferably, the present invention also performs dust suction during laser etching.
[0014] In a second aspect, the present invention provides a cadmium telluride power generation glass, the structure of which comprises, from bottom to top, a glass substrate, a transparent conductive film, a window layer, a cadmium telluride absorption layer, a back contact layer and a back electrode, wherein the cadmium telluride absorption layer is obtained by the above-mentioned surface treatment method.
[0015] Preferably, the material of the back contact layer is ZnTe doped metal material.
[0016] Preferably, the metal material is selected from any one or more of Ag, Cu, Hg and Au.
[0017] Preferably, the metal doped in the ZnTe-doped metal material is co-doped with Ag and Cu.
[0018] Preferably, the Ag metal element doping concentration is 100 ppm to 500 ppm. In some embodiments of the present invention, the Ag metal element doping concentration is any one of 100 ppm, 300 ppm, 500 ppm, or a value in between.
[0019] Preferably, the doping concentration of the Cu metal element is 0.2-3%wt. In some embodiments of the present invention, the doping concentration of the Cu metal element is any one of 0.2%wt, 1%wt, 3%wt, or a value in between.
[0020] Preferably, the thickness of the back contact layer is 5-30 nm. In some embodiments of the present invention, the thickness of the back contact layer is any one of 5 nm, 10 nm, 30 nm, or a value in between.
[0021] In a third aspect, the present invention provides a method for manufacturing cadmium telluride power generation glass, comprising the following steps:
[0022] (1) depositing a window layer on a glass substrate covered with a transparent conductive film;
[0023] (2) depositing a cadmium telluride absorption layer on the window layer, wherein the cadmium telluride absorption layer is treated by the above-mentioned surface treatment method;
[0024] (3) depositing a back contact layer on the surface-treated cadmium telluride absorption layer, and performing a heat treatment after the deposition;
[0025] (4) Depositing a back electrode on the heat-treated back contact layer.
[0026] Preferably, the heat treatment is performed under an inert gas or vacuum state.
[0027] Preferably, the temperature of the heat treatment is 200-300° C. In some embodiments of the present invention, the temperature of the heat treatment is any one of 200° C., 240° C., 300° C., or a value in between.
[0028] Preferably, the heat treatment time is 10 to 60 minutes. In some embodiments of the present invention, the heat treatment time is any one of 10 minutes, 30 minutes, 60 minutes, or a value in between.
[0029] The beneficial effects of the present invention are:
[0030] The present invention uses laser etching to process the oxide layer on the surface of the cadmium telluride absorption layer, effectively removing the oxide layer so that the absorption layer presents a pyramid-shaped velvet structure to form a light-trapping structure, which can improve the high-quality ohmic contact between the absorption layer and the back contact layer, enhance light absorption, reduce series resistance, and thus enhance the performance of the cadmium telluride power generation glass.
[0031] The present invention reasonably adjusts the laser parameters to adjust the cadmium telluride absorption layer to form a pyramid-shaped velvet structure, ensuring that the height of the velvet structure is 5 to 80 nm, thereby ensuring that the bottom surface has a lower reflectivity and achieving a better light trapping effect. At the same time, the area of the back contact layer is increased. Good contact with the back contact layer can reduce series resistance and help further improve power generation efficiency.
[0032] The back contact film layer material of the power generation glass of the present invention is obtained by using ZnTe doped metal material. The metal elements in the film react with the Te-rich layer or CdTe to generate a telluride degenerate semiconductor that is conducive to CdTe ohmic contact, and can form a thin Schottky barrier with the back electrode. Photogenerated carriers can pass through the CdTe surface through the tunneling effect to reach the back electrode.
[0033] In the process of preparing the power generation glass of the present invention, heat treatment is required after the back contact layer is deposited to promote the reaction and diffusion of the back contact layer and improve the contact characteristics.
[0034] The power generation glass of the present invention has high power generation efficiency, high filling factor, high conversion efficiency, excellent comprehensive performance, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a structural diagram of the power generation glass of the present invention.
[0036] Figure 2 This is a comparison chart of the conversion efficiency of the power generation glass prepared in the embodiment and the effect example of the present invention. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solution of the invention, the present invention is further described in detail below in conjunction with specific implementation methods.
[0038] Example 1
[0039] The structure of the power generation glass provided in this embodiment is as follows Figure 1 As shown, from bottom to top are a glass substrate 1, a transparent conductive film 2, a window layer 3, a cadmium telluride absorption layer 4, a back contact layer 5, and a back electrode 6. The cadmium telluride absorption layer 4 has a pyramid-shaped suede structure.
[0040] The method for making the power generation glass in this embodiment is as follows:
[0041] (1) Depositing a CdSe window layer with a thickness of 150 nm on a glass substrate covered with a transparent conductive film (TCO);
[0042] (2) depositing a 3100 nm cadmium telluride absorption layer on the CdSe window layer, and using laser to etch the oxide layer on the surface of the cadmium telluride absorption layer, so that the cadmium telluride absorption layer forms a pyramid-shaped velvet structure, and the vertical height of the velvet structure is 60 nm; wherein the parameters of the laser are: a pulsed laser with a wavelength of 532 nm, a circular spot, a pulse width of the pulsed laser of 150 nm, a frequency of the pulsed laser of 55 KHz, and a scanning speed of the pulsed laser of 7000 mm / s;
[0043] (3) depositing a back contact layer on the surface treated cadmium telluride absorption layer, the back contact layer thickness is 10 nm, and after deposition, heat treatment is performed in an inert gas environment at a temperature of 300° C. for 30 min; the back contact layer material is ZnTe doped with Ag and Cu, wherein the Ag metal element doping concentration is 500 ppm, and the Cu metal element doping concentration is 1% wt;
[0044] (4) A back electrode with a thickness of 80 nm is deposited on the heat-treated back contact layer.
[0045] Example 2
[0046] The structure and manufacturing method of the power generation glass provided in this embodiment are the same as those in embodiment 1, except that:
[0047] The vertical height of the velvet structure in step (2) is 45nm; the parameters of the laser are: a pulsed laser with a wavelength of 532nm, a circular spot, a pulse width of 200nm, a frequency of 40KHz, and a scanning speed of 6000mm / s.
[0048] Example 3
[0049] The structure and manufacturing method of the power generation glass provided in this embodiment are the same as those in embodiment 1, except that:
[0050] The vertical height of the velvet structure in step (2) is 80nm; the parameters of the laser are: a pulsed laser with a wavelength of 532nm, a circular spot, a pulse width of 300nm, a frequency of 60KHz, and a scanning speed of 9000mm / s.
[0051] Example 4
[0052] The structure and manufacturing method of the power generation glass provided in this embodiment are the same as those in Embodiment 1, except that:
[0053] The vertical height of the velvet structure in step (2) is 5 nm; the parameters of the laser are: a pulsed laser with a wavelength of 532 nm, a circular spot, a pulse width of 100 nm, a frequency of 20 KHz, and a scanning speed of 3000 mm / s.
[0054] Example 5
[0055] The structure and manufacturing method of the power generation glass provided in this embodiment are the same as those in embodiment 1, except that:
[0056] In step (3), the thickness of the back contact layer is 30 nm, the material of the back contact layer is ZnTe doped with Ag, wherein the doping concentration of the Ag metal element is 300 ppm, the heat treatment temperature is 240° C., and the time is 60 min.
[0057] Example 6
[0058] The structure and manufacturing method of the power generation glass provided in this embodiment are the same as those in Embodiment 1, except that:
[0059] In step (3), the thickness of the back contact layer is 5 nm, the material of the back contact layer is ZnTe doped with Ag, wherein the doping concentration of the Ag metal element is 100 ppm, the heat treatment temperature is 200° C., and the time is 10 min.
[0060] Example 7
[0061] The structure and manufacturing method of the power generation glass provided in this embodiment are the same as those in Embodiment 1, except that:
[0062] The doping concentration of Cu metal element in step (3) is 0.2%wt.
[0063] Example 8
[0064] The structure and manufacturing method of the power generation glass provided in this embodiment are the same as those in Embodiment 1, except that:
[0065] The doping concentration of Cu metal element in step (3) is 3%wt.
[0066] Comparative Example 1
[0067] The structure and manufacturing method of the power generation glass provided in this comparative example are the same as those in Example 1, except that:
[0068] The vertical height of the velvet structure in step (2) is 150nm; the parameters of the laser are: a pulsed laser with a wavelength of 1064nm, a circular spot, a pulse width of 50nm, a frequency of 10KHz, and a scanning speed of 10000mm / s.
[0069] Comparative Example 2
[0070] The structure and manufacturing method of the power generation glass provided in this comparative example are the same as those in Example 1, except that:
[0071] In step (3), the back contact layer material is ZnTe, the heat treatment temperature is 100° C., and the time is 5 minutes.
[0072] Effect example: Electric glass performance test
[0073] The performance of the power generation glass produced in the embodiment and the comparative example was tested. The results are shown in Table 1, and the comparison chart of conversion efficiency is shown in Figure 2 .
[0074] Table 1
[0075]
[0076] From Table 1 and Figure 2It can be seen that the power generation glass produced by the embodiment of the present invention can improve the high-quality ohmic contact between cadmium telluride and the back contact layer, reduce the series resistance and increase the short-circuit current, and form a light-trapping structure by laser etching to improve light absorption, thereby improving the performance of cadmium telluride power generation glass. If the laser parameters exceed the range specified by the present invention, and the height of the obtained velvet structure exceeds the range specified by the present invention, as shown in Comparative Example 1, the current density, conversion efficiency and fill factor of the power generation glass are reduced. In addition, the selection of the back contact layer material is also very important. The power generation performance of the back contact layer material obtained by doping ZnTe with metal in the present invention is significantly better than that of Comparative Example 2, which uses only ZnTe as the back contact layer material.
[0077] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A surface treatment method for a cadmium telluride absorption layer, characterized in that: Laser etching is used to etch the oxide layer on the surface of the cadmium telluride absorption layer, so that the cadmium telluride absorption layer forms a pyramid-shaped velvet structure, and the vertical height of the velvet structure is 5 to 80 nm.
2. The surface treatment method of the cadmium telluride absorption layer according to claim 1, characterized in that: The laser is a pulse laser with a wavelength of 532 nm.
3. The surface treatment method of the cadmium telluride absorption layer according to claim 2, characterized in that: The pulse width of the pulse laser is 100-300 nm.
4. The surface treatment method of the cadmium telluride absorption layer according to claim 2, characterized in that: The frequency of the pulse laser is 20-60 KHz.
5. The surface treatment method of the cadmium telluride absorption layer according to claim 2, characterized in that: The pulse laser scanning speed is 3000-9000 mm / s.
6. A cadmium telluride power generation glass, characterized in that: The structure comprises, from bottom to top, a glass substrate, a transparent conductive film, a window layer, a cadmium telluride absorption layer, a back contact layer and a back electrode, wherein the cadmium telluride absorption layer is obtained by the surface treatment method according to any one of claims 1 to 5.
7. The cadmium telluride power generation glass according to claim 6, characterized in that: The material of the back contact layer is ZnTe doped metal material.
8. The cadmium telluride power generation glass according to claim 7, characterized in that: The metal material is selected from any one or more of Ag, Cu, Hg and Au.
9. A method for manufacturing cadmium telluride power generation glass, characterized in that: The following steps are involved: (1) depositing a window layer on a glass substrate covered with a transparent conductive film; (2) depositing a cadmium telluride absorption layer on the window layer, wherein the cadmium telluride absorption layer is treated by the surface treatment method according to any one of claims 1 to 5; (3) depositing a back contact layer on the surface-treated cadmium telluride absorption layer, and performing a heat treatment after the deposition; (4) Depositing a back electrode on the heat-treated back contact layer.
10. The manufacturing method according to claim 9, characterized in that: The temperature of the heat treatment is 200-300°C.
Citation Information
Cited By
Cadmium telluride absorption layer with specific pattern structure and solar cell preparation method
CN122340903A
A cadmium telluride absorption layer of a specific pattern structure and a solar cell manufacturing method
CN122340903B